2001
DOI: 10.1002/1097-4636(20010605)55:3<277::aid-jbm1015>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive bone cement: Effect of silane treatment on mechanical properties and osteoconductivity

Abstract: A novel bioactive bone cement (GBC) was developed with newly designed bioactive MgO-CaO-SiO(2)-P(2)O(5)-CaF(2) glass beads as the inorganic filler and high molecular weight poly(methyl methacrylate) as the organic matrix. The purpose of this study was to examine the relationship between the amount of the silane coupling agent (gamma-methacryloxy propyl trimethoxy silane) used to treat the glass beads and the mechanical and biological properties of the resultant bone cement. Serial changes in the cement over ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 21 publications
3
47
0
Order By: Relevance
“…Another study showed that in the absence of -methacryloxy propyl trimethoxy silane (MPS), the glass-based cement was more brittle than PMMA cement. However, the bending strength of glass-based cements increased more than the PMMA cements after being treated with 0.1% of MPS [57]. In addition, the glass filler size and content are both important to determine the mechanical properties and osseointegration of the cements in vivo.…”
Section: Bioactive Glass Fillersmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that in the absence of -methacryloxy propyl trimethoxy silane (MPS), the glass-based cement was more brittle than PMMA cement. However, the bending strength of glass-based cements increased more than the PMMA cements after being treated with 0.1% of MPS [57]. In addition, the glass filler size and content are both important to determine the mechanical properties and osseointegration of the cements in vivo.…”
Section: Bioactive Glass Fillersmentioning
confidence: 99%
“…MPS not only helps inorganic fillers to form strong covalent bonds with an organic matrix but it also provides Si-OH groups to induce heterogeneous nucleation of the apatite on their surface [67,68]. Therefore, mechanical properties and osseointegration of bone ce- ments improve after being treated with MPS, but a slight increase in setting time has also been observed [57,69].…”
Section: Other Active Gradientsmentioning
confidence: 99%
“…The flexural properties of only a few IBCs have been reported 25, 96, 97. Values of these properties for cements from all classes of IBCs are needed.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…The method has also been used for coupling hydroxyapatite in bone cements. 11,12 Deb et al 13 have reported the use of silane coupling agents to bind polyethylene to hydroxyapatite to improve mechanical properties. However, the stability of such a linkage is debatable in an aqueous environment and as a consequence the choice of silane coupling agents in this application is not ideal.…”
Section: Introductionmentioning
confidence: 99%